SUNAN KALIJAGA'S LEGACY UNDER THE SHADOW OF MALADMINISTRATION: INSTITUTIONAL CONFLICT IN THE SEMARANG–DEMAK TOLL ROAD PROJECT - Raden Aditya Permana Agung; Bangkit A. Wiryawan (Journal of Politic and Government Studies, 2026)
The development of toll road infrastructure under Indonesia's National Strategic Project aims to promote economic growth and public welfare. However, land acquisition frequently generates conflicts, particularly involving waqf land. The dispute over the Sunan Kalijaga waqf land in Kadilangu, Demak Regency, reflects institutional fragmentation, overlapping authority, and alleged maladministration in compensation distribution. This study analyzes the conflict dynamics during the land acquisition process for the Semarang–Demak Toll Road and examines how inter-institutional conflicts of interest contributed to institutional disharmony. This research employs a qualitative case study with socio-legal and historical juridical approaches. Primary data were collected through field observations, while secondary data were obtained from literature, legal documents, and historical archives. Data were analyzed inductively through data reduction, data presentation, and conclusion drawing. The findings reveal that the dispute was primarily driven by institutional fragmentation, overlapping authority, and inconsistent government policies in determining the legitimate foundation and nadzir authorized to manage waqf assets and receive compensation. These conditions transformed the dispute into a structural and administrative conflict. Furthermore, conflicts of interest among institutions created institutional disharmony, reflected in differing interpretations of legal authority, institutional representation, and decision-making. As a result, inter-institutional coordination weakened and hindered the effective resolution of the waqf land dispute.